Intuitionistic Fuzzy g Semi Continuous Mapping and Irresolute Function in Intuitionistic Fuzzy Topological Spaces - Missier, S. Pious; Arokiaraj, A. Peter; S.Jackson (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The purpose of this paper is to introduce and study the concepts of Intuitionistic Fuzzy Semi Continuous Mapping and Intuitionistic Fuzzy Semi Irresolute Function in Intuitionistic Fuzzy Topological Spaces and some of their characterizations are discussed. Additionally, we examine its driving effects by contrasting them with known irresolute functions and continuous mappings. A thorough verification has been carried out using relevant cases for the irresolute function and continuity mentioned above.